Percepção das barreiras e motivações para o tratamento adequado de pacientes com Diabetes Mellitus tipo 1 e tipo 2 assistidos ambulatorialmente na Universidade Federal do Triângulo Mineiro - TOMÉ, Janaíne Machado (2019)
INTRODUCTION: Diabetes Mellitus is a chronic disease that has been presenting an alarming growth and has a significant impact on the life of the individual. It is of utmost importance that the patient understands the need to maintain metabolic control to prevent the complications that arise over the years due to uncontrolled control. The vision of the patient as a whole is essential to help him overcome the adversities that diabetes generates in his personal and family routine. OBJECTIVES: The present study was carried out with the objective of evaluating the main barriers and motivations that interfere in the metabolic control of patients with type 1 and type 2 Diabetes Mellitus. METHODS: This is a cross-sectional descriptive study of a quantitative approach, conducted at the Diabetes Outpatient Clinic of the Federal University of Triângulo Mineiro Hospital of Clinics. For data collection, the following instruments were used: Identification Form, Laboratory Tests for metabolic control, Socioeconomic Classification Questionnaire and Study Questionnaire on Barriers and Motivations Related to People with Diabetes, consisting of 62 questions, divided into 5 domains related to barriers: Education and Self-Knowledge, Health Systems, Social Group, Physical Barriers and Psychological Barriers, and 1 Motivation domain. Continuous variables were analyzed for normality through the Kolmogorov – Smirnov test and homogeneity of variances was verified by the Levene test. The descriptive results were expressed in measures of central tendency (mean and median) and dispersion (standard deviation, minimum and maximum). The differences were considered significant at the level of 5% (p ≤ 0.05) or between 5 and 6% (borderline - 0.05 <p< 0.06). The analyses were conducted using SPSS version 23 software. RESULTS: We evaluated 132 patients, 31 with DM1 and 101 with DM2. For the group with DM1, there was a predominance of females (67.7%), aged between 18 and 67 years (median: 31). When assessing barriers, most patients (93.5%) has knowledge about the disease itself, 100% understands that the lack of control cancause complications and it finds important to incorporate diet and physical exercises in the treatment routine, 38.7% adhered to the diet and 64.5% practice physical activity. Checking appointments and returns is no problem for 80.6%, however, 83.9% have difficulty obtaining medicines and tapes. The family assists 77.4% of the patients, the presence of symptoms resulting from diabetes does not prevent 80.6% of patients from controlling the disease and 71.0% already accepted the fact of being diabetic. When evaluating the factors that most motivate, 80.6% cited the family, 64.5% self-esteem and 58.0% the religion. For the group with DM2 there was an even greater predominance of females (75.2%), with ages between 30 and 91 years (median: 63). When assessing barriers, most patients (84.2%) has knowledge about the disease itself, 99.0% understands that the lack of control can cause complications and 98.0% think it important to incorporate diet and physical exercises in the treatment routine, 25.7% adhered to the diet and 47.5% practice physical activity. Checking appointments and returns is no problem for 81.2%, however, 50.5% have difficulty obtaining inputs. The family assists 67.4% of the patients, the presence of symptoms resulting from diabetes does not prevent 88.1% of patients from controlling the disease and 86.1% already accepted the fact of being diabetic. When evaluating the factors that most motivate, 75.3% cited the family, 73.3% selfesteem and 56.5% the religion. CONCLUSION: It was observed that patients are aware of the disease and have a good observation. Among the barriers are the difficulty in accepting the disease and and adhering to a proper eating routine and healthier lifestyle, the difficulty in obtaining inputs, the lack of support from family and friends. Among the factors that most motivate the patients are self-esteem, family dependence and spirituality/religiosity, reinforcing the important role of these factors in the acceptance and good metabolic control.